Development Development of Social Studies Teaching Materials Based on Local Potential in Cepu Region for Middle School Students in Blora - Nurita, Lilin (Program Studi S1 Pendidikan IPS, Universitas Negeri Surabaya, 2022)
The purpose of this study was to produce teaching materials in the form of modules based on the local potential of the Cepu area on the material